“The Jimmy Hoffa of Canada”: Hal Banks and a Comparative Perspective on Union Corruption - Witwer, David (Labour / Le Travail, 2022)
This article compares the union careers of the US Teamsters Union leader James R. Hoffa and the head of the Canadian Seafarers International Union (siu), Hal Banks. It focuses on the charges of union corruption that swirled around both men in the late 1950s and early 1960s. The article uses that comparison to consider the predominant understanding of union corruption in the United States, which posits a kind of American exceptionalism in regard to this issue. The similarities and differences between the cases of Hoffa and Banks provide a new consideration of the history of union corruption in Canada. This comparison also offers a new perspective on the divergence between unionization rates in the United States and Canada since 1964.